The Effect of Parenting Style, Communication Patterns, and Self Efficacyon Adolescent Participation in Family Decision Making - Megawat Simanjuntak; Risda Rizkillah (SEA-CECCEP, 2020)
Adolescence is between childhood and adulthood, where many different developmental tasks must be completed. One of the tasks of adolescent development is to make decisions that in the process, involve parents. This study aims to analyze parenting style, communication patterns and self-efficacy on adolescent participation in family decision making. The research design used was a cross-sectional study design. The population of this research is teenagers from grade 10 to grade 12 who attend SMAN 4 Kota Bogor and SMAN 1 Leuwiliang, Bogor Regency. Sampling in this study was carried out randomly in groups (random cluster sampling) with 323 samples. Data is collected by self-administered. The results showed that the sample self-efficacy included in the moderate category, parents in urban and rural areas had a high authoritative parenting style. Family communication patterns still low. Youth participation in family decision making belongs to the moderate category. One factor that influence a significant negative effect on adolescent participation in decision making was conformity orientation communication patterns. Parents have an essential role in helping improve the ability of children in decision making. Parents begin to involve children in making decisions and build balanced family communication patterns with the orientation of the child and following parents.